Professional skills development in a resource-poor setting: the case of pharmacy in Malawi - Lim, Zoe; Anderson, Claire; McGrath, Simon (Elsevier, 2012)
The dominance of the human capital approach in vocational skills development has been increasingly questioned for being de-humanised and de-contextualised. Contrary to this trend, the discourse in health professional skills development has shown increasing enthusiasm for consolidating this existing paradigm. To debate whether professional skills development should indeed be insulated from such scepticism, this paper examines one strategy adopted by the health professions. Called ‘task shifting’, this strategy involves re-delegating professional tasks to nonprofessional cadres according to a skills-based toolkit. Challenging the context-free approach to using this toolkit, this paper presents ethnographic evidence derived from a case study of pharmacy workforce issues in Malawi. It was found that task shifting was inhibited by a perception barrier about the moral and intellectual superiority of the pharmacists. Pharmacy technicians were judged to be unfit for a professional task because of a perceived lack of professional status, power and ethics. On tracing the origin of the inherent professional prowess assigned to the pharmacists, it was found that professionalism was an ideology borrowed from external sources, inter alia, colonial legacies and global health governance. This study exposes our hidden assumption about an axiomatic transferability of Anglo American skills development models to a postcolonial, aid-dependent context. This paper therefore suggests redefining this toolkit by bridging health research into dialogue with non-health disciplinary concerns such as postcolonialism and aiddependence. In conclusion, it argues that professional skills development is context-laden; and in need of a human-centred approach that involves true indigenousparticipation–challenges not unlike those faced by the vocational skills discourse.